Lecture notes : immunology - Todd, Ian , 1954-; Spickett, Gavin (Wiley-Blackwell / John Wiley & Sons, 2010)
Designed as an introductory core text on immunology, Lecture Notes: Immunology successfully provides a concise and student-friendly review of essential immunity and immunopathology topics. Key concepts are introduced in an incremental fashion and build up a thorough overview of the field for the reader.